Improving MSMEs Quality Towards Digitalization and Building an Innovative Community: A Case Study of Independent Community Service Program in Bhakti Karya Village, Binjai Selatan - Novien Rialdy (Athallah Publishing Globalndo, 2025)
Micro, Small, and Medium Enterprises (MSMEs) form the backbone of the national economy, including in Bhakti Karya Village, Binjai Selatan Sub-district, Binjai City. However, the majority of MSMEs in this area still operate traditionally, facing serious constraints in adopting digital technology for marketing and minimal financial literacy, especially concerning investment. This situation hinders business competitiveness and the potential for local economic growth. Community service aims primarily to initiate the transformation of local MSMEs through comprehensive assistance. The core focus is on implementing digital marketing and increasing basic investment literacy insights to encourage business sustainability and create a competitive and innovative community. This service learning research utilized a qualitative Participatory Action Research approach. Activities were conducted over 30 days at the partner location. The study objects included four specific MSMEs Bamboo Crafts, Tempeh Processing, Chicken Feet Snacks, and Sponge Cake as well as the surrounding community. The implementation method involved three stages: observation, socialization and training, and evaluation and continuous mentoring. The program implementation demonstrated significant success. 100% of the partner MSMEs were successfully integrated into digital platforms (WhatsApp Business and Instagram), accompanied by training in creating visual product content. Furthermore, the socialization of basic investment concepts (such as savings vs. gold investment) provided new insights into business capital management. Supporting activities in the form of tutoring also successfully boosted the learning spirit of children in the Bhakti Karya Village environment.